2022
DOI: 10.1155/2022/6808648
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Application Value of PBL Combined with Situational Simulation Teaching Method in Clinical Practice Teaching of Radiology Department

Abstract: Objective. To study the application value of PBL (Problem-Based Learning) combined with a situational simulation teaching method in clinical practice teaching of radiology. Methods. 120 interns who practiced in the radiology department of our hospital from 2020 to 2021 were randomly divided into a study group and a control group. The research group used PBL combined with the scenario simulation teaching method to carry out clinical practice teaching activities. The control group was carried out according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Both PBL and SBL possess their own strengths and weaknesses; when used together, they can augment overall learning effectiveness and quality. 45 In practical scenarios, selecting appropriate learning methods and tools should be based on specific objectives, content, and student characteristics to provide personalized high-quality educational experiences. As technology continues to advance, SBL is expected to play an increasingly vital role in education by contributing considerably to talent development and societal progress.…”
Section: Discussionmentioning
confidence: 99%
“…Both PBL and SBL possess their own strengths and weaknesses; when used together, they can augment overall learning effectiveness and quality. 45 In practical scenarios, selecting appropriate learning methods and tools should be based on specific objectives, content, and student characteristics to provide personalized high-quality educational experiences. As technology continues to advance, SBL is expected to play an increasingly vital role in education by contributing considerably to talent development and societal progress.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This process involves students taking on different roles in each scenario to complete a series of tasks, guided and evaluated by the teachers overseeing the process (Han, 2022). So far, SST has been widely used in the training of professionals associated with English (Abdyhalykova, 2016), Chinese (Chang, Chen, & Liao, 2020), Management (Chen, 2019) and Nursing (Pu & Yang, 2022;Gong, et al, 2022), but their application in the teaching of organic chemistry has rarely been reported. Therefore, this study explored the application of SST to an organic chemistry class.…”
mentioning
confidence: 99%